A five-microRNA signature predicts survival and disease control of patients with head and neck cancer negative for HPV infection - Heß, Julia; Unger, Kristian; Combs, Stephanie; Debus, Jürgen; Grosu, Anca-Ligia; Linge, Annett; Rödel, Claus; Stuschke, Martin; Zips, Daniel; Zitzelsberger, Horst; Ganswindt, Ute; Henke, Michael; et al. (Clinical cancer research, 2019)
Purpose: Human papillomavirus (HPV)-negative head and neck squamous cell carcinoma (HNSCC) is associated with unfavorable prognosis, while independent prognostic markers remain to be defined. Experimental Design: We retrospectively performed miRNA expression profiling. Patients were operated for locally advanced HPV-negative HNSCC and had received radiochemotherapy in eight different hospitals (DKTK-ROG; n = 85). Selection fulfilled comparable demographic, treatment, and follow-up characteristics. Findings were validated in an independent single-center patient sample (LMU-KKG; n = 77). A prognostic miRNA signature was developed for freedom from recurrence and tested for other endpoints. Recursivepartitioning analysis was performed on the miRNA signature, tumor and nodal stage, and extracapsular nodal spread. Technical validation used qRT-PCR. An miRNA-mRNA target network was generated and analyzed. Results: For DKTK-ROG and LMU-KKG patients, the median follow-up was 5.1 and 5.3 years, and the 5-year freedom from recurrence rate was 63.5% and 75.3%, respectively. A five-miRNA signature (hsa-let-7g-3p, hsamiR- 6508-5p, hsa-miR-210-5p, hsa-miR-4306, and hsa-miR-7161-3p) predicted freedom from recurrence in DKTK-ROG [hazard ratio (HR) 4.42; 95% confidence interval (CI), 1.98-9.88, P < 0.001], which was confirmed in LMU-KKG (HR 4.24; 95% CI, 1.40-12.81, P = 0.005). The signature also predicted overall survival (HR 3.03; 95% CI, 1.50-6.12, P = 0.001), recurrence-free survival (HR 3.16; 95% CI, 1.65-6.04, P < 0.001), and disease-specific survival (HR 5.12; 95% CI, 1.88-13.92, P < 0.001), all confirmed in LMU-KKG data. Adjustment for relevant covariates maintained the miRNA signature predicting all endpoints. Recursive- partitioning analysis of both samples combined classified patients into low (n = 17), low-intermediate (n = 80), high-intermediate (n = 48), or high risk (n = 17) for recurrence (P < 0.001). Conclusions: The five-miRNA signature is a strong and independent prognostic factor for disease recurrence and survival of patients with HPV-negative HNSCC.
Gesehen am 04.04.2019